Paradigma Baru dalam Audit Internal - Irawan, Ronny (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2003)
The changes of business environment caused transformation of the role of internal auditing in any organization. In traditional concept, the role of internal auditor is a faultfinder, perform reperforming, and then move away to control as a focus, finally to add value and improve an organization' operations. They represent as a Part of organization provides a service of value to the organization, as a consultant and helps an organization accomplish its objectives. This new paradigms gives opportunities and challenges for internal auditor to improve their knowledge's and skills broadly.